Listen to the Voices of Unwed Teenage Mothers in Malaysian Shelter Homes: An Explorative Study - Saim, Nor Jana (Glob J Health Sci, 2013)
This qualitative research aims to explore the daily life experiences of Malaysian unwed teenage mothers in shelter homes. The research is based on the thematic analysis of interviews with seventeen respondents aged from 12 to 18 years. Eight sub-themes described the experience of the unwed teenage mothers in the shelter home and led to three overall themes: rules and regulations, relationship with the staff and relationship with the other girls at the shelter home. The findings indicated that the shelter homes involved were not fulfilling the standard of the Malaysian national laws and United Nations Convention on the Rights of the Child. We strongly suggest that the authorities provide a clear guideline concerning the implementation of Malaysian national laws and United Nations Convention on the Rights of the Child.